Geometrical Illustrations of Newlands' and Mendelejeff's Periodic Law of the Atomic Weights of the Chemical Elements - Haughton, Samuel (1889)
A reprint of an article that was first published in the Proceedings of the Royal Irish Academy, series III, volume I.
Keywords: Periodic law; Chemical elements; Atomic weights